Gambaran histopatologik lambung tikus Wistar (Rattus norvegicus) yang diberikan air perasan jeruk nipis (Citrus aurantifolia) - Laomo, Suhaidir; Loho, Lily L.; Kairupan, Carla F. (e-Biomedik, 2016)
Abstract: Lime squash is often used as a herbal remedy for gastritis, even though it is acidic. It contains citric acid and vitamin C which in certain doses can be irritant to the stomach. Nevertheless, lime squash also contains antioxidants such as limonene, flavonoids, and vitamin C, that play certain roles in improving the protection of the stomach and the ability of cell regeneration, and as anti-inflammatory agents. This study aimed to reveal the histopathological features of the gaster of Wistar rats (Rattus norvegicus) treated with lime squash. This was an experimental laboratory study using 15 adult Wistar rats divided into three groups (five rats in each group). Group A (negative control) was given no treatment; group B and C were treated with lime squash 0.5 and 1.56 ml/day, respectively. Lime squash was given in a single dose for seven consecutive days. Rats were terminated on day eight. The results revealed that the gaster of Wistar rats in group A were similar to that of the normal gaster, while group B and C showed no signs of inflammation and the gastric gland cells appeared enlarged and dense. Conclusion: Histopathological features of the gaster of Wistar rats, treated with either low or high dose (three-fold) lime squash, showed no signs of abnormalities such as inflammation, however, there were enlarged glandular cells which might be related to increased gastric mucosal defence.Keywords: lime, gastric histopathological features, inflammatory cells, gastric glandsÂ Abstrak: Air perasan jeruk nipis sering digunakan sebagai obat herbal terhadap gastritis, meskipun bersifat asam. Air perasan jeruk nipis mengandung asam sitrat yang pada dosis tertentu menjadi bahan iritan terhadap lambung. Namun demikian, kandungan antioksidan seperti limonene, flavonoid dan vitamin C berperan dalam meningkatkan proteksi lambung dan kemampuan regenerasi sel, serta sebagai anti inflamasi. Penelitian ini bertujuan untuk mengetahui gambaran histopatologik lambung tikus wistar yang diberikan air perasan jeruk nipis. Jenis penelitian ialah eksperimental menggunakan 15 ekor tikus Wistar yang dibagi dalam tiga kelompok (lima ekor tikus tiap kelompok). Kelompok A (kontrol negatif) tidak diberi perlakuan; kelompok B dan C masing-masing diberi air perasan jeruk nipis 0,5 ml/hari dan 1,56 ml/hari dosis tunggal selama tujuh hari, Semua tikus diterminasi pada hari ke-8. Hasil yang didapatkan pada gambaran histopatologik lambung tikus wistar yaitu: kelompok A sesuai dengan gambaran lambung normal; kelompok B dan C tidak menunjukkan tanda-tanda peradangan namun sel-sel kelenjar lambung tampak membesar dan padat. Simpulan: Gambaran histopatologik lambung tikus wistar yang diberi air perasan jeruk nipis, baik dosis rendah maupun tinggi (tiga kali lipat) tidak menunjukkan tanda-tanda kelainan seperti peradangan, melainkan tampak terjadi pembesaran sel-sel kelenjar lambung yang mungkin berhubungan dengan peningkatan pertahanan mukosa lambung. Kata kunci: jeruk nipis, gambaran histopatologik lambung, sel radang, kelenjar lambung